The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fphar.2022.885527
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of Lysine Methyltransferase and Arginine Methyltransferase in Kidney Diseases

Abstract: Methylation can occur in both histones and non-histones. Key lysine and arginine methyltransferases under investigation for renal disease treatment include enhancer of zeste homolog 2 (EZH2), G9a, disruptor of telomeric silencing 1-like protein (DOT1L), and protein arginine methyltransferases (PRMT) 1 and 5. Recent studies have shown that methyltransferases expression and activity are also increased in several animal models of kidney injury, such as acute kidney injury(AKI), obstructive nephropathy, diabetic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…EZH2, a histone-lysine N-methyltransferase enzyme, has been identified as an important therapeutic target to treat renal tubulointerstitial fibrosis (16). EZH2 is up-regulated in several animal models of renal fibrosis and pharmaceutically inhibition of EZH2 ameliorates renal tubulointerstitial fibrosis (17). Recent study showed that EZH2 is a direct target of triptolide and thus we hypothesized that triptolide inhibits renal fibrosis by targeting EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…EZH2, a histone-lysine N-methyltransferase enzyme, has been identified as an important therapeutic target to treat renal tubulointerstitial fibrosis (16). EZH2 is up-regulated in several animal models of renal fibrosis and pharmaceutically inhibition of EZH2 ameliorates renal tubulointerstitial fibrosis (17). Recent study showed that EZH2 is a direct target of triptolide and thus we hypothesized that triptolide inhibits renal fibrosis by targeting EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…Histone methylation refers to the transfer of up to three methyl groups from the common methyl donor S‐adenosyl‐L‐methionine (SAM) to lysine or arginine residues of histones (Horiuchi et al., 2013 ; Rungratanawanich et al., 2023 ). Histone methyltransferases can be generally classified into three different classes: SET domain‐containing N‐lysine methyltransferases, disruptor of telomeric silencing 1‐like (DOT1L) with lysine as its substrate, and protein arginine transferases (PRMTs) which result in methylation of arginine (Horiuchi et al., 2013 ; Zhou et al., 2022 ). According to the products generated, all PRMTs can be divided into two subtypes: Type I PRMTs, including PRMT1, 3, and 4 that generate asymmetric dimethylarginine; and Type II PRMTs, including PRMT 5 and 7 that generate symmetric dimethylarginine.…”
Section: How Do Hallmarks Of Aging Participate In the Pathogenesis Of...mentioning
confidence: 99%
“…731 PRMT and PKMT can not only catalyze the methylation of histones, but also catalyze the methylation of nonhis-tone proteins. 732 For example, the DNA damage response proteins MRE11 and 53BP1 can be methylated by PRMT1 to regulate its DNA exonuclease activity and localization at DNA damage sites. 733 Some immunomodulatory proteins, such as Vav1 and NIP45, can also be modified by arginine methylation.…”
Section: Methylationmentioning
confidence: 99%